KEUNGGULAN PRIVATE LABEL DIBANDINGKAN MEREK NASIONAL PADA RITEL HYPERMARKET - TANNUR, IVANA FAUSTINE (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
Nowdays private label products has become something of a trend among retailers, its penetration of private label products in the community is still terhadang by the presence of a national brand. This is because Indonesia because the public still believed that national brands have good value for money is greater than the private label products. Therefore authors interested in writing more about the comparison between private label and national brands as well as the advantages of private label compared to national brands. The presence of private label products is very profitable because consumers get cheaper than products labeled national. In many cases other retailers who are able to use the power of prtvate label may cause bargaining on a national brand. Discount private label can take market share from national brands, and when national brands lowered its price will make the private label market share loss. The prerogative of the retailers in determining the display of goods in the shops to distinguish the rivalry between national and private label brands from competition among national brands, because the retailer has a kepututusan last so that it can enter the private label among national brands. The largest private label market a private label quality can be compared to national brands that have high quality. At the beginning of the national brand competition with private label, it was clear that private label has a harder time to gain market share in the category dominated by leading brands being advertised.